Feeding behavior of the mudclam anodotia edentula (linne. 1758.). - Edano, Donna Marie Carino (1999.)
Using the indirect method of determining food processing, the effect of light and algal feed on the feeding behavior of the mudclam Anodontia edentula was determined. Direct light lowered the mudclam's filtration rate, while total darkness resulted to a much higher filtering activity. Hence, total darkness was considered as the optimum condition for feeding. In terms of total number of cells removed from suspension, Isochrysis galbana was the preferred algal species. This could be because Isochrysis galbana is comparatively smaller than Chaetoceros calcitrans and contains a much higher amount of polyunsaturated fatty acid
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Mudclam; Anodontia edentula (Linne, 1758)